Carbon quantum dots/TiO2 composites for efficient photocatalytic hydrogen evolution - Yu, Huijun; Zhao, Yufei; Zhou, Chao; Shang, Lu; Peng, Yong; Cao, Yinhu; Wu, Li-Zhu; Tung, Chen-Ho; Zhang, Tierui (Journal of materials chemistry. A, Materials for energy and sustainability, 2014)
Carbon quantum dots modified P25 TiO₂ composites (CQDs/P25) with a “dyade”-like structure were prepared via a facile one-step hydrothermal reaction. CQDs/P25 exhibited improved photocatalytic H₂ evolution under UV-Vis and visible light (λ > 450 nm) irradiation without loading any noble metal cocatalyst, compared to pure P25. A possible mechanism of the photocatalytic H₂ production activity over CQDs/P25 was proposed based on detailed measurements of the transient photocurrent response, surface photovoltage and hydroxyl radicals. CQDs play dual roles on the improved photocatalytic activity of CQDs/P25. Under UV-Vis light irradiation CQDs act as an electron reservoir to improve the efficient separation of the photoinduced electron–hole pairs of P25. However, under visible light irradiation CQDs act as a photosensitizer to sensitize P25 into a visible light response “dyade” structure for H₂ evolution.